Field Assessment of Onion Genotypes for Resistance against Purple Blotch Complex (Alternaria porri And Stemphylium vesicarium) under Artificial Epiphytotic Conditions in Indian Punjab - Yadav, Ritesh Kumar; Singh, Amarjit; Dhatt, Ajmer Singh; Jain, Sandeep (International Journal of Applied Sciences and Biotechnology, 2017)
A total of forty one genotypes of onion were evaluated for their relative response to purple blotch complex caused by Alternaria porri and Stemphylium vesicarium under artificial epiphytotic condition in field during Rabi 2014-2015 and 2015-2016. Significant variation in disease severity among the onion genotypes was found over two years but the pooled analysis revealed that most of the variations were due to genotype x year interaction. None of the genotypes exhibited resistance to the disease complex. Of the test genotypes, eighteen were found moderately susceptible while twenty one were found susceptible to the disease complex. Two genotypes viz., Punjab Naroya and OSR-1364 exhibited highly susceptible reaction. However, six genotypes viz., P-96, P-30, P-121, OSR-1359, P-98 and OSR-1370 showed superior yield performance. Purple blotch complex exhibited highly significant negative correlation of 0.71 and 0.67 with fresh bulb yield and bulb size, respectively. Cluster analysis of onion genotypes was performed based on disease and yield variables and the genotypes were furthered grouped into five clusters based on average values of disease and yield variables. Int. J. Appl. Sci. Biotechnol. Vol 5(4): 498-504